Dukungan Sosial dan Religiusitas Dalam Penyesuaian Diri Mahasiswa Perantau - Tugimin Supriyadi; Mega Widyastuti; Aulia Yasmin Salsabilla; Mochamad Widjanarko (Jurnal Psikologi Perseptual)
This study aims to determine whether there is an influence of the variables Social support and Religiosity on Self Adjustment in students who migrate to Bekasi. Based on the phenomenon that migrant students will always meet, interact, and communicate with fellow migrants and the native community, it will cause cultural diversity and changes in students so that the demands to adjust themselves increase. In order to be able to carry out good Self Adjustment in a migrant state, Social support and Religiosity may have an influence. This study has three hypotheses, namely there is an influence between Social support and Self Adjustment in students who migrate (H1); there is an influence between Religiosity on the relationship between Self Adjustment in students who migrate (H2); and there is a relationship between Social support and Religiosity on Self Adjustment in students who migrate (H3). The research method used is quantitative with a descriptive approach. Based on the results of this study, it can be concluded that there is an influence between Social support and Self Adjustment; there is no influence between Religiosity and Self Adjustment; and there is an influence between Social support and Religiosity on Self Adjustment in migrant students in Bekasi.